C diskTutor [L. John Ribar]. - Ribar, L. John. (Berkeley, [Calif.] : Osborne McGraw-Hill, 1992)
A self-teaching guide to the fundamentals of the standard ANSI C language. Includes a special introductory version of the WATCOM C compiler (with a compiler, linker, and run-time libraries), an editing environment, and three full and eight mini case studies.
Title from disk label.
System requirements: IBM-compatible PC; 640K RAM; MS-DOS 3.0 or higher; hard disk with 2.5MB free space.
Keywords: C (Computer program language) -- Software